Isotropic and anisotropic elasto-plastic coupling in clays: a thermodynamic approach. (1st July 2022) - Rollo, Fabio; Amorosi, Angelo
Abstract: In many solids, like soils and rocks, the elastic behaviour exhibited for very small stress/strain perturbations often depends on the previously experienced plastic dissipative processes: this is commonly referred to as elasto-plastic coupling. In this paper, this phenomenon is examined in a thermodynamic-based constitutive modelling perspective. Within the framework of hyperplasticity theory, a new formulation considering isotropic and rotational hardening is proposed to illustrate two forms of isotropic and anisotropic elasto-plastic coupling for clays. The thermodynamic approach allows some specific features of the phenomenon to be highlighted in more detail as compared to what conventionally derived from the elasto-plasticity theory, with particular reference to the effects of coupling on the yield domain in the Cauchy stress space and the resulting non-associated flow rules. The predictive capability of the model is illustrated with reference to a series of numerical simulations of real and ideal laboratory tests on reconstituted clays.